2021
DOI: 10.1111/jpn.13545
|View full text |Cite
|
Sign up to set email alerts
|

Feeding rice fermented beer waste improves growth performance, nutrient digestibility and nitrogen utilization in growing rabbits

Abstract: This study was conducted to investigate the effects of dietary rice brewer waste (RBW) on growth performance, nutrient utilization and nitrogen balance in growing rabbits. Thirty growing rabbits (758 ± 25.7 g initial body weight) were randomly assigned to control and four treatment groups (containing RBW) in a completely randomized design with six rabbits per group. The study lasted 6 weeks for measurements of feed intake and growth performance followed by a five‐day metabolic trial to determine nutrient diges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The Ile and Arg contents in beef from the R1 and R2 groups were higher than those in the control group, but the difference was not significant, indicating that different amino acids in feed have varied conversion efficiencies ( 37 ). Another possible reason is that FMDG contain probiotics that bind with epithelial cells of stomach and bowels and help to synthesize the amino acids which result in improving the content of amino acids in beef ( 15 , 38 , 39 ). We detected 17.13–21.23 g/100 g of total amino acid (TAA) content in beef; including 7 essential amino acids (EAAs): threonine (Thr), valine (Val), methionine (Met), Ile, Leu, phenylalanine (Phe) and Lys at 7.09–8.68 g/100 g, and 7 non-essential amino acids (NEAAs): Asp, serine (Ser), Glu, proline (Pro), glycine (Gly), alanine (Ala), and tyrosine (Tyr) at 8.24–10.22 g/100 g ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Ile and Arg contents in beef from the R1 and R2 groups were higher than those in the control group, but the difference was not significant, indicating that different amino acids in feed have varied conversion efficiencies ( 37 ). Another possible reason is that FMDG contain probiotics that bind with epithelial cells of stomach and bowels and help to synthesize the amino acids which result in improving the content of amino acids in beef ( 15 , 38 , 39 ). We detected 17.13–21.23 g/100 g of total amino acid (TAA) content in beef; including 7 essential amino acids (EAAs): threonine (Thr), valine (Val), methionine (Met), Ile, Leu, phenylalanine (Phe) and Lys at 7.09–8.68 g/100 g, and 7 non-essential amino acids (NEAAs): Asp, serine (Ser), Glu, proline (Pro), glycine (Gly), alanine (Ala), and tyrosine (Tyr) at 8.24–10.22 g/100 g ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The dry matter, crude protein, neutral detergent fiber, and acid detergent fiber contents of Moutai DG are 30.46%, 21.84% DM, 36.85% DM, and 24.72% DM, respectively, according to our preliminary analysis, and the amino acid content is high, indicating that Moutai DG is a good feed resource. Previous studies found that fermented distillers' grains contain probiotic culture, prebiotic and postbiotic properties that are useful for growth performance ( 15 ). Numerous studies have examined the nutritional value of dry DG and its effects on livestock feeding and found that adding an appropriate amount of DG to the diets of cattle did not affect feed efficiency, growth performance and meat quality ( 16 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the primary objectives of adding fermented feeds to animal diets (including rabbits [30], poultry [31], geese [32], ducks [15], and pigs [33]) is to enhance growth performance. Previous research has consistently shown that feeding animals with fermented feeds positively impacted their growth, promoted weight gain [34], and improved feed conversion rates [32].…”
Section: Growth Performancementioning
confidence: 99%
“…These by -products have high nutritional values, such as high concen-trations of protein, fat and minerals (lIU, 2011). The wet brewery residue is rich in crude protein (CP) at an average of 25%, has high levels of crude fiber (FB) at an average of 20% and a total digestible nutrient (TND) index of 74%, comparable to other traditional foods (KlAGENBOECH et al, 2012).…”
Section: Introductionmentioning
confidence: 99%